Regulation of the Ride-sharing Business Model: International Experience and Lessons for Vietnam - Quang, Hoang Ngoc (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 1 No 4, 2021)
Nowadays, sharing economy business models (SEBMs) have taken a very important role in the economy in Vietnam. These models have ameliorated the quality of life by reducing travel costs, increasing the quality of transportation services, and lessening unemployment, especially after the COVID-19 crisis. Among these SEBMs, the ride-sharing business model has many development opportunities. It has appeared in many countries and has efficiently supported economic growth. However, many problems also arise during the development of this model, including worker’s rights, driver licensing, and unfair competition with traditional companies. These issues bring about conflicts in society, especially between ride-sharing companies and traditional taxi companies. Meantime, the old regulation mechanisms have not been suitable with challenges related to this new business model. Thailand, Singapore and the UK are countries that have long-standing legal systems. With experience of management from these countries, this study explains some ride-sharing model issues in Vietnam and suggests some policies, especially on regulations for ride-sharing companies, ride-sharing drivers, and tax liability of these companies.